Undirected (Solitary) Birdsong in Female and Male Blue-Capped Cordon-Bleus (Uraeginthus cyanocephalus) and Its Endocrine Correlates - Geberzahn, Nicole (Public Library of Science, 2011)
BACKGROUND: Birdsong is a popular model system in research areas such as vocal communication, neuroethology or neuroendocrinology of behaviour. As most research has been conducted on species with male-only song production, the hormone-dependency of male song is well established. However, female singing and its mechanisms are poorly understood. METHODOLOGY/PRINCIPAL FINDINGS: We characterised the song and its endocrine correlates of blue-capped cordon-bleus (Uraeginthus cyanocephalus), a species in which both sexes sing. Like other estrildids, they produce directed song during courtship and undirected (or solitary) song in isolation, i.e. when the mate is not visible or absent. We compare solitary song of blue-capped cordon-bleus to published descriptions of the song of its relative, the zebra finch (Taeniopygia guttata). Solitary song of cordon-bleus shared some overall song features with that of zebra finches but differed in spectro-temporal song features, sequential stereotypy and sequential organisation. The song of cordon-bleus was dimorphic with respect to the larger size of syllable repertoires, the higher song duration and the lower variability of pitch goodness (measuring the pureness of harmonic sounds) in males. However, in both sexes the overall plasma testosterone concentrations were low (ca. 300 pg/ml) and did not correlate with the sexually dimorphic song motor pattern. Despite such low concentrations, the increase in the rate of solitary song coincided with an increase in the level of testosterone. Furthermore, the latency to start singing after the separation from the mate was related to hormone levels. CONCLUSIONS/SIGNIFICANCE: Our findings suggest that the occurrence of solitary song but not its motor pattern might be under the control of testosterone in female and male cordon-bleus.